Kontribusi Kearifan Lokal Dalam Mewujudkan Pemilu Damai - Muhammad Arif; Endang Ekowati; Muhammad Syahwali; Shela Myta Wahyudi (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
The theoretical dominance of direct local election is mainly based on western theory of democracy, local politics and development. There are plenty western theories used to analyze current Indonesian local politics, including direct local election. In fact, however, the problems of local direct election still take place in many forms of disadvantages. These problems are, for instance, money politics, riots, long conflicts, black campaigns and so forth. In order to minimize these problems, local wisdom based on Javanese values is important in contribution to solve the relevant problems. There are many Javanese value based local wisdom that may useful to be implemented. Keywords: local direct elections, local wisdom, Javanese values, local politics.